Green finance in Viet Nam: Barriers and solutions - Trong Co Nguyen; Anh Tu Chuc; Le Ngoc Dang (Asian Development Bank Institute (ADBI), 2018)
Viet Nam's energy sector has made considerable strides in recent years in achieving high percentage of nationwide electrification and a relatively diversified energy mix that is dominated by hydropower, followed by gas and coal. However, sustaining those achievements including addressing gradually depleted domestic resources, keeping pace with growing energy demand from the energy-intensive economy and meeting ambitious climate change targets under the Nationally determined contributions in Paris Agreement need to call large sums of new investment, particularly in renewables. If those necessary investments are not satisfied, it will further increase Viet Nam's dependence on imported coal to cater its future energy needs with substantial negative environmental, health, climate change and economic consequences. Based on the existing challenges, the authors make recommendations including establishing more conducive conditions for private investment and strengthening the domestic funding environment through a functional financial market.
Keywords: F21; H23; Q42; Q54; Q58; 330; renewable energy; green finance; energy security; Viet Nam